HALITOSIS. METHODS OF DIAGNOSIS, TREATMENT AND PREVENTION - Ohista Makhmudova; Shukurova N.T. (Journal of new century innovations, 2024)
Annotation. Halitosis (bad breath) is a disease of polyetiological nature, widely common among adults and children, difficult to eliminate with breath freshening drugs [1, 2]. The problem of halitosis has both medical and psychological aspects. Halitosis can be an indicator of the pathology of various organs and systems of the body, also halitophobia, this is a false sensation by the patient of something unpleasant bad breath, which have a huge negative impact on social activity and quality of life of people century, is the reason for limiting human communication [1]. There are three fundamentally different states associated in the patient’s consciousness or in the perception of the environment.